Nitric oxide induces rice tolerance to excessive nickel by regulating nickel uptake, reactive oxygen species detoxification and defense-related gene expression. (January 2018) - Rizwan, Muhammad; Mostofa, Mohammad Golam; Ahmad, Muhammad Zulfiqar; Imtiaz, Muhammad; Mehmood, Sajid; Adeel, Muhammad; Dai, Zhihua; Li, Zheyong; Aziz, Omar; Zhang, Yihui; Tu, Shuxin
Abstract: Soil contamination with nickel (Ni) is a persistent threat to crop production worldwide. The present study examined the putative roles of nitric oxide (NO) in improving Ni-tolerance in rice. Our findings showed that application of exogenous sodium nitroprusside (SNP), a NO donor, significantly improved the growth performance of rice seedlings when grown under excessive Ni. The enhanced Ni-tolerance of rice prompted by SNP could be ascribed to its ability to regulate Ni uptake, decrease Ni-induced oxidative stress as evidenced by reduced levels of hydrogen peroxide, malondialdehyde, and electrolyte leakage in Ni-stressed plants. The positive roles of NO against Ni-toxicity also reflected through its protective effects on photosynthetic pigments, soluble proteins and proline. SNP also boosted antioxidant capacity in Ni-stressed plants by maintaining increased levels of ascorbate, enhanced activities of ROS-detoxifying enzymes, particularly peroxidase (POD) and catalase (CAT) in both roots and shoots compared with Ni-stressed alone plants. Moreover, SNP treatment also upregulated the transcript levels of CAT, POD, ascorbate peroxidase, glutathione reductase and superoxide dismutase genes in shoots under Ni-stress. Using different sulfide compounds and NO scavenger cPTIO, we also provided evidence that NO, rather than other byproducts of SNP, contributed to the improved performance of rice seedlings under Ni-stress. Collectively, our results conclude that exogenous SNP-mediated modulation of endogenous NO enhanced rice tolerance to Ni–stress by restricting Ni accumulation, maintaining photosynthetic performance and reducing oxidative damage through improved antioxidant system, thereby suggesting NO as an effective stress regulator in mitigating Ni-toxicity in economically important rice, and perhaps in other crop plants. Highlights: Nickel (Ni) and nitric oxide (NO) interaction was examined in rice seedlings. Ni-induced toxic effects reflected in growth performance of rice seedlings. NO reduced Ni uptake and reversed growth defects of rice plants under Ni stress. NO-triggered antioxidant capacity alleviated oxidative damage under Ni-stress.